Underwater investigations standard practice manual - Childs, Kenneth M. (American Society of Civil Engineers, 2001)
Annotation "This manual provides guidance for those involved in underwater structural inspection. It presents guidelines representing standards of practice, documentation and reporting, and administrative considerations for various inspection types, including new construction, baseline, routine, repair design, special, repair construction and post-event inspections." "The first of several extensive appendices provides guidelines for the inspection of unique underwater structure types, including bridges, open-piled structures, gravity and retaining structures, marinas, hydraulic structures, pipelines and conduits, dry docks, locks and gates, floating structures, breakwaters, tower bases, moorings and anchors, tanks and storage facilities, and cathodic protection systems. Subsequent appendices include types and causes of defects and deterioration commonly found in underwater concrete structures, steel structures, wooden structures, masonry structures, composite structural components, and undermining and scour; references for obtaining in-depth information on the structure types; and an extensive glossary of key terms."--BOOK JACKET.Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.
Errata inserted.
Keywords: Offshore structures -- Inspection -- Handbooks, manuals, etc.; Ocean engineering.; elektronické knihy; electronic books